Investigation of creep damage mechanical behaviors of red sandstone considering temperature effect. Issue 2 (27th October 2021) - Pan, Xiaokang; Berto, Filippo; Zhou, Xiaoping
Abstract: This work investigates the influence of high temperature on the creep damage behaviors of red sandstone. The closure and evolution of microcracks in the red sandstone treated at different temperatures during the enter creep process are analyzed. Temperature has obvious influence on uniaxial compressive strength, Young's modulus, and failure modes of red sandstone. It can degrade the mechanical behaviors of red sandstone and can reduce the ability of red sandstone to resist creep deformation. Moreover, acoustic emission (AE) technology is employed to monitor the distribution law of the AE events generated at each creep stage. As the temperature increases, the absolute value of the critical index increases exponentially, reflecting the exponential increase in the proportion of its low‐energy AE signal. HIGHLIGHTS: The temperature can degrade the mechanical behaviors of red sandstone. Temperature reduces the ability of red sandstone to resist creep deformation. The probability density of AE absolute energy satisfies the Gutenberg–Richter law. The absolute value of critical index increases exponentially with an increase in temperature.